Idiopathic Haemolacria in a 9 Year Old Girl (TAJ: Journal of Teachers Association, 2019)
Haemolacria or bloody tears is a rare clinical condition caused by various ocular and systemic conditions; some cases may be drug-induced and some are idiopathic. We are reporting a case admitted with recurrent bilateral idiopathic haemolacria. A 9-year old girl was admitted in our hospital with complaints of recurrent spontaneous bloody tears from both eyes for 1 month. There were no other bleeding manifestations. Blood stained discharge from punctum was not observed during compression of either nasolacrimal duct. Psychiatric assessment and ENT examination were normal. Further evaluations for underlying causes were unremarkable. There was no abnormality on the ophthalmological and radiological investigations. The patient was diagnosed as a case of idiopathic haemolacria. Patients presenting with complaints of bloody tears should be evaluated with a detailed history focusing on etiologic factors, ocular examination, and nasal and paranasal examination.TAJ 2018; 31(1): 70-72